Ethnic differences in serum adipokine and C-reactive protein levels: The Multiethnic Cohort - Morimoto, Yukiko (Int J Obes (Lond), 2014)
BACKGROUND: Ethnic disparities in metabolic disease risk may be the result of differences in circulating adipokines and inflammatory markers related to ethnic variations in obesity and body fat distribution. SUBJECTS/METHODS: In a cross-sectional design, we compared serum levels of leptin, adiponectin, C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) in control subjects (321 men and 930 women) from two nested case-control studies conducted within the Multiethnic Cohort Study consisting of whites, Japanese Americans (JA), Latinos, African Americans (AA), and Native Hawaiians (NH). General linear models were applied to evaluate ethnic differences in log-transformed serum biomarker levels before and after adjusting for body mass index (BMI) at cohort entry. RESULTS: In comparison to whites, significant ethnic differences were observed for all biomarkers except TNF-α. JA men and women had significantly lower leptin and CRP levels than whites and JA women also had lower adiponectin levels. Leptin was significantly higher in AA women (p<0.01), adiponectin was significantly lower in AA men and women (p=0.02 and p<0.001), and CRP and IL-6 were significantly higher in AA men and women. Lower adiponectin (p<0.0001) and CRP (p=0.03) levels were the only biomarkers in NH women that differed from whites; no statistically significant differences were seen for NH men and for Latino men and women. When adjusted for BMI at cohort entry, the differences between the lowest and highest values across ethnic groups decreased for all biomarkers except adiponectin in men indicating that ethnic differences were partially due to weight status. CONCLUSIONS: These findings demonstrate ethnic variations in circulating adipokine and CRP levels before and after adjustment for BMI. Given the limitation of BMI as a general measure of obesity, further investigation with visceral and subcutaneous adiposity measures are warranted to elucidate ethnicity-related differences in adiposity in relation to disparities in obesity-related disease risk.